Ghosts ghouls other nightmares : spooky stories - Kemp, Gene. (New York : Puffin Books, 1995)
A spine-chilling collection of stories about ghosts by established authors including Ray Bradbury, Robert Westall, and Joan Aiken.
"First published in Great Britain under the title: The Puffin book of Ghosts and Ghouls by Viking...1992"--T.p. verso.
Young Adult
Keywords: Ghost stories; Ghost stories